Determinants of profitability in Indonesian Islamic banks: Financial and macroeconomic insights - Nisa', Khilyatun; Andriansyah, Yuli; Hasan, Barham Bakr (Universitas Islam Indonesia, 2023)
IntroductionProfitability is a crucial indicator of financial sustainability and competitiveness in the banking industry. For Islamic banks, profitability is influenced by both internal financial management and external macroeconomic factors, shaped by their adherence to Sharia principles. Indonesian Islamic banks operate in a dynamic financial environment that presents unique challenges and opportunities for sustaining profitability.ObjectivesThis study examines the determinants of profitability in Indonesian Islamic banks, focusing on the effects of internal financial ratios—Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and operating efficiency (BOPO)—as well as external factors such as interest rates and inflation.MethodA quantitative approach was employed, analyzing secondary data from 12 Islamic banks in Indonesia over the 2014–2018 period. Multiple regression analysis was used to evaluate the relationships between these variables and profitability, measured by Return on Assets (ROA). Diagnostic tests ensured the robustness and validity of the statistical model.ResultsThe findings reveal that FDR positively influences profitability, while NPF and BOPO have significant negative effects. CAR and inflation show no significant impact, and interest rates indirectly affect profitability despite the interest-free nature of Islamic banking. These results highlight the interplay of internal management practices and macroeconomic factors in shaping financial performance.ImplicationsThis study emphasizes the need for Islamic banks to enhance credit risk management, optimize operational efficiency, and adapt to macroeconomic conditions to sustain profitability. The findings provide actionable insights for policymakers, regulators, and practitioners aiming to strengthen the financial sustainability of Islamic banking in Indonesia.Originality/NoveltyThis research integrates internal and macroeconomic determinants to offer a comprehensive analysis of profitability in Indonesian Islamic banks. By bridging gaps in the literature, it contributes to the development of strategies for financial performance optimization in Sharia-compliant banking.